Communicating science to motivate action: A case study of birds and climate change - Wilsey, Chad B.; Bateman, Brooke; Pomper, Liz; Bogo, Jennifer; Shepherd, Robyn (Frontiers in Climate, 2022)
Climate change is an existential threat to biodiversity and people, but building political will for action on climate change remains elusive. Research on climate change communications to increase effectiveness at motivating action include these recommendations: pairing risk and opportunity in message framing, localizing information, and appealing to a sense of place. Here, we present a case study on mobilizing bird enthusiasts to take action on climate change. The science communicated found that over two-thirds of North American birds are moderately or highly vulnerable to climate change under a 3.0°C warming scenario. Of these climate-vulnerable species, 76% would have reduced vulnerability if warming were stabilized at 1.5°C. These findings were summarized and communicated with the public in an award-winning interactive website, the “Birds and Climate Visualizer,” that allowed individuals to look up any location by postal ZIP code and learn what birds would be impacted by climate. Also included was a Climate Action Handbook providing sample personal actions. The communications rollout earned 2.5 billion media impressions, the visualizer has been used at least 42,000 times, and handbook circulated to 250,000 households. More than 33,000 people read headlines from the report or explored the visualizer and then completed an online action in support of clean energy policies. The message frame combined with the visualizer and handbook as tools to deliver the frame have contributed to climate legislative wins in four states. These early successes suggest that message and visual online tools that localize and personalize a message are effective to motivate action.